Food Dependent Exercise-Induced Anaphylaxis in pediatric age. Can we trust the oral food challenge with exercise and acetylsalicylic acid? FDEIA, can we trust augmented OFC? - Miceli Sopo, Stefano; Gelsomino, Mariannita; Del Vescovo, Ester; Bersani, Giulia (Acta Biomedica Atenei Parmensis, 2020)
Food-dependent exercise-induced anaphylaxis (FDEIA) is an IgE-mediated allergy resulting from the combination of the ingestion of an offending food and physical exercise. According literature, oral food challenge (OFC) followed by physical exercise (OFCPE) should be considered the diagnostic gold standard. In the absence of adverse reactions, other cofactors should be added (e.g. acetylsalicylic acid, alcohol in adulthood), one at a time. But many other factors increase patient’s reactivity. This could reduce the sensitivity of the OFCPE and, consequently, make instructions for patients less reliable. On the other hand, the addition of cofactors not reported by the patient may reduce test specificity. With the help of two exemplary stories, that present opposite outcomes, diagnostic difficulties of FDEIA are discussed.